Thicker is Better? Synthesis and Evaluation of Well-Defined Polymer Brushes with Controllable Catalytic Loadings - Fernandes, Antony E.; Dirani, Ali; d'Haese, Cécile; Deumer, Gladys; Guo, Weiming; Hensenne, Peter; Nahra, Fady; Laloyaux, Xavier; Haufroid, Vincent; Nysten, Bernard; Riant, Olivier; Jonas, Alain M. (Chemistry : a European journal, 2012)
Polymer brushes (PBs) have been used as supports for the immobilization of palladium complexes on silicon surfaces. The polymers were grown by surface‐initiated atom‐transfer radical polymerization (SI‐ATRP) and postdecorated with dipyridylamine (dpa) ligands. The pendant dpa units were in turn complexed with [Pd(OAc)2] to afford hybrid catalytic surfaces. A series of catalytic samples of various thicknesses (ca. 20–160 nm) and associated palladium loadings (ca. 10–45 nmol cm−2) were obtained by adjusting the SI‐ATRP reaction time and characterized by ellipsometry, X‐ray reflectivity, X‐ray photoelectron spectroscopy, and inductively coupled plasma mass spectrometry (ICP‐MS). ICP‐MS revealed a near‐linear relationship between thickness of the polymer brush and palladium content, which confirmed the robustness of the preparation and postmodification sequence presented herein, rendering possible the creation of functional architectures with predefined catalytic potential. The activities of the catalytic PBs were determined by systematically exploring a full range of substrate‐to‐catalyst ratios in a model palladium(0)‐catalyzed reaction. Quantitative transformations were observed for loadings down to 0.03 mol % and a maximum turnover number (TON) of around 3500 was established for the system. Comparison of the catalytic performances evidenced a singular influence of the thickness on conversions and TONs. The limited recyclability of the hairy catalysts has been attributed to palladium leaching. Hairy catalysts! Polymer brushes (PBs) have been used as platforms for the construction of well‐defined catalytic surfaces (see scheme; PHEMA=poly(2‐hydroxyethyl methacrylate), dpa=dipyridylamine) by using a simple, robust, post‐modification sequence. Varying the PB thickness allows accurate control over catalyst loadings. The effect of PB thickness on activity (conversions, turnovers) has carefully been examined.